Hunting down NLRP3 inflammasome: An executioner of radiation-induced injury - Cheng, Han; Chen, Lingling; Huang, Minchun; Hou, Jin; Chen, Zhifeng; Yang, Xiaojun (Frontiers in Immunology, 2022)
Radiotherapy is one of the mainstream treatment modalities for several malignancies. However, radiation-induced injury to surrounding normal tissues limits its efficacy. The NLRP3 inflammasome is an essential mechanism of innate immunity that reacts to challenges from endogenous danger signals and pathological microbes. A growing body of evidence has demonstrated a key role of NLRP3 inflammasome in the pathogenesis of radiation-induced tissue injury. Despite accumulating evidence, the potential value of the NLRP3 inflammasome in the management of radiation-induced tissue injury is not adequately recognized. We conducted a literature review to characterize the relationship between NLRP3 inflammasome and radiation injury. By analyzing recent evidence, we identify NLRP3 inflammasome as one of the executioners of radiation-induced injury, since it responds to the challenges of radiation, induces cell pyroptosis and tissue dysfunction, and initiates non-resolving inflammation and fibrosis. Based on these concepts, we propose early intervention/prevention strategies targeting NLRP3 inflammasome in a radiation context, which may help resolve imperative clinical problems.